Description of a new species and complementary description of a known species of Iphiseiodes De Leon (Acari: Phytoseiidae) - de Carvalho Mineiro, Jeferson Luiz; de Castro, Tatiane Marie Martins Gomes; de Moraes, Gilberto José (Zootaxa, 2011)
Species of Iphiseiodes De Leon have been reported only from tropical and subtropical regions of the Americas. In this paper, a new species of this genus is described from southeastern Brazil and a complementary description is provided for Iphiseiodes saopaulus (Denmark & Muma).